Analisis Etis Atas Kebenaran Dan Tanggung Jawab Dalam Dunia Komunikasi Sosial - William Chang (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2011)
Abstract: There is no society without social communication. One of the key roles of social communication is to promote truth and responsibility in a multicultural society. Everybody has his/her right to get true information from the field of communication. Being responsible for all activities in one’s social communication is a main obligation of a good communicator. The main goal of this article is to analyse the real situation of the mass communication in daily life. Those who get involved in the the field of social communication need to know more about the true meaning of truth and reponsibility so that they can respect the values of truth and responsibility in this field. Keywords: Social communication, truth, responsibility, pluralistic society, secret, common good, mutual respect, justice, peace, the dignity of the human person. Abstrak: Tiada masyarakat tanpa komunikasi sosial. Salah satu peran kunci komunikasi sosial adalah memajukan kebenaran dan tanggung jawab dalam sebuah masyarakat majemuk. Setiap pribadi memiliki hak untuk memperoleh informasi yang benar dalam bidang komunikasi sosial. Bertanggung jawab atas semua kegiatan dalam bidang komunikasi sosial adalah sebuah kewajiban utama seorang komunikator yang baik. Situasi komunikasi sosial yang sesungguhnya dalam hidup harian menjadi tujuan utama artikel ini. Mereka yang terlibat dalam bidang komunikasi sosial perlu mengetahui lebih banyak tentang makna sejati dari kebenaran dan tanggung jawab sehingga mereka dapat menghargai nilai-nilai kebenaran dan tanggung jawab dalam bidang ini.